1991
DOI: 10.1177/39.10.1940304
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ca2+ transients in norepinephrine-stimulated individual H-35 hepatoma cells: fura-2 digital imaging microscopy and high time-resolution microspectrofluorometry.

Abstract: We investigated spatiotemporal changes in cytoplasmic free Ca2 concentration ([Ca2 Jj) in norepinephrine (NE)-stimulated and fura-2-loaded individual H-35 rat hepatoma cells, using digital imaging microscopy and high time-resolution microspectrofluorometry. Application of NE (5 x 10 M) resulted in an initial transient increase in [Ca2 jj, followed by a small sustained [Ca2 Ji plateau above the pre-stimulaiion level. The initial peak and the small sustained plateau originated from intracellular stores and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This result suggested that AR-42J has a a-adrenergic receptor. Recently, we have reported that rat hepatoma cell line, H-35, has a aadrenergic receptor (23). It is interesting to point out here that AR-42J cells contain a-adrenergic receptor, because no norepinephrine action to pancreatic exocrine acinar cell has been reported so far as we know.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This result suggested that AR-42J has a a-adrenergic receptor. Recently, we have reported that rat hepatoma cell line, H-35, has a aadrenergic receptor (23). It is interesting to point out here that AR-42J cells contain a-adrenergic receptor, because no norepinephrine action to pancreatic exocrine acinar cell has been reported so far as we know.…”
Section: Resultsmentioning
confidence: 90%
“…Weused a digital imaging microscopy system for Ca2+mesure-ment, which is composedof inverted microscope IMT-2RFL with a color image analyzer, CIA-102 (OLYMPUS, Japan) and equipped with an OSP-2 microspectrofluorometer as described previously (21). The system was improved by changing the light source from a mercury lamp to a 75Wxenon lamp (23). Emission wavelength was 510 nm, while the excitation wavelength was 340 nm/380 nm.…”
mentioning
confidence: 99%